Kajian Biaya Operasional Kendaraan dan Nilai Waktu Perjalanan Sepeda Motor pada Jalan Medan-Banda Aceh Kota Lhokseumawe - Fitri, Gustina; Ismail, Ismail; Abdullah, Faisal (Politeknik Negeri Lhokseumawe, 2025)
Medan-Banda Aceh Road is a road that connects Lhokseumawe city with other cities, Aceh province with North Sumatra, Lhokeumawe city with various strategic centers such as roads in and out of housing, offices, hospitals, gas stations, UNIKI campus, STIES campus, Akper campus, campus Akbid, STAIN campus, PNL campus and so on. So at certain times there are often traffic jams due to side obstacles which result in large Vehicle Operation Costs (BOK) and hampered travel time. This research aims to analyze vehicle operating costs and the value of travel time for private vehicles on these roads, so that a comparison of the benefits of vehicle operating costs and travel time value can be found. The method used to analyze vehicle operating costs is the Pacific Consultant International (PCI) method and Travel Time Value uses the Running Speed Approach method. From the calculation results, the total average vehicle operating costs for Medan-Banda Aceh Road during peak hours, namely for private cars at post 1, is IDR. 5,946 / kend and post 2, namely Rp. 5,975 / kend. The value of post 1 travel time is IDR. 73,321/hour, and in post 2 it is IDR. 76,851/hour, but side obstacles must be regulated so that traffic jams do not occur which will affect the amount of vehicle operating costs and the value of travel time.